School health program: from the secular training to the contemporary ministerial institution - Maier, S. R. O.; Tabosa, M. N.; Santos, B. S.; Mendes, S. S.; Oliveira, W. S. (Scientific Electronic Archives, 2018)
To verify in the official texts emitted by Department of Education , Health department and scientific literature, by means of manuscripts published in periodic as if gave to the process of structuring and implantation of the Program Health in the School. A study is about revision narrative on the basis of official documents, with sights to congregate information related to the quarrels, implementation and implementation of the respective program. The quarrels had remained in the understanding of history and the context politician with respect to the health in the pertaining to school context until the institution of the Program of Health in the School.